Factors related to the persistence of nursing students studying at the faculty of nursing, university of Ubon Ratchathani - เมืองซอง, วราลักษณ์; เพ็ญวิเชียร, ณัฐริกา; ราชาฐา, ณัฐวิภา; บัวกอ, ทิพย์สุคนธ์; ถิ่นอำนาจ, วรรณภา; บุทฤทธิ์, ธนบูรณ์; มะณีวงษ์, ธัญวลัย; ประไพเพชร, ธนัญญา; ศรียัง, ศศิวิภา; ชัยวรรณวรรต, ทศา (Journal of Ratchathani Innovative Health Sciences, 2019)
The objective of this study was to study the factors related to the persistence of nursing students studying in the faculty of nursing at Ratchathani University. A study sample was selected from nursing student enrolled in the first through fourth year in the second semester of 2017. Approximately 243 persons comprised the stratified random sampling. The study utilized a general information questionnaire, a questionnaire for studying factors in the faculty of nursing and a questionnaire for the persistence of nursing students in the faculty of nursing studies. The reliability of the study data is 0.92. The data was analyzed using, mean, percentage and standardized deviation to test the relationship of variables with Pearson's correlation. The statistical significance level was 0.01. The results showed that factors related to the persistence of nursing students studying at the faculty of nursing, university of Ubon Ratchathani overall, it was at a high level ( = 4.06, S.D. = 0.53). When considering each aspect, it was found that the factor of love in nursing profession was at the high level ( = 4.12, S.D. = 0.57). Secondly, the correlation coefficient was at high level ( = 4.10, S.D. = 0.55). And the economic factor was moderate ( = 3.96, S.D. = 0.47). The retention of nursing students in nursing education at the University of Ubon Ratchathani overall, indicated a high level ( = 4.17, S.D.=0.51). These Factors were identified in the faculty of nursing at Ratchathani University. There was a positive correlation with the persistence of nursing students in nursing education. The statistical significance was 0.01. The three factors measured were; first, relationships, reported a high level of (r = 0.75). Second, the love for the nursing profession, the relationship was a level (r = 0.73). The last factor was economic, the relationship was (r = 0.52). The results of the study are based on the hypothesis of the research.